Immunocytochemical localization of fibrinogen, platelet factor 4, and beta thromboglobulin in thin frozen sections of human blood platelets. - Sander, H J (1983)
Affinity-purified monospecific antibodies against human fibrinogen and the platelet-specific proteins platelet factor 4 and beta thromboglobulin were used to localize these antigens in thin and ultra-thin frozen sections of mildly fixed, washed human blood platelets. By immunofluorescent double-labeling experiments the distribution of fibrinogen was compared to that of platelet factor 4 and beta thromboglobulin. All three antigens occurred in virtually all platelets and showed and identical, dotlike distribution. For immunoelectron microscopy we used protein A-colloidal gold on ultra-thin frozen sections to visualize the specific reaction indirectly. The staining for platelet factor 4, beta thromboglobulin, and fibrinogen localized exclusively over alpha-granules of washed platelets. Within the granules, platelet factor 4 was localized preferentially in the electron dense, alpha-granule nucleoid, whereas fibrinogen was more predominant in the electron-lucent granule periphery. Beta thromboglobulin localization did not show a preferential intragranular distribution.